Coeliac disease and psychiatric comorbidity: epidemiology, pathophysiological mechanisms, quality-of-life, and gluten-free diet effects. (3rd September 2017) - Cossu, Giulia; Carta, Mauro Giovanni; Contu, Federico; Mela, Quirico; Demelia, Luigi; Elli, Luca; Dell'Osso, Bernardo
Abstract: Coeliac Disease (CD) is an autoimmune disease in which an environmental factor, gluten, triggers a pathological reaction. It results in intra- and entra-intestinal manifestations of disease, including, most frequently, diarrhoea, weight loss, and anaemia. CD occurs in ∼1% of the western population, being one of the most common autoimmune lifelong disorders, and may present with a variety of psychiatric comorbidities. Psychiatric comorbidity in CD often complicates the diagnosis, reduces the quality-of-life, and worsens the prognosis of affected patients. This review summarizes the epidemiological studies that underline this connection, and focuses on the potential mechanisms related to this comorbility, such as nutritional deficiencies, immune responses, interference in brain processes, and dysfunctions in the gut–brain axis. Factors that play a central role on patients' quality of life, psychological well-being and adherence are presented. Finally, evidence of regression in psychiatric symptoms following the introduction of a gluten-free diet is underlined as well.